Kejadian Bullying dan Kepercayaan Diri Pada Remaja - Eka Oktavianto; Dina Wahyu Melinda; Endar Timiyatun (STIKes Surya Global Yogyakarta, 2023)
Background of Study: Bullying is a phenomenon that occurs primarily in teens especially in school. It can take the form of physical, verbal, social, cyber and mental/psychological. Have a teenager being a victim of bullying, it can affect the formation of his or her self-confidence. The aim of this research is to clarify the relationship between bullying and self-confidence in Al-Irsyad Tawangmangu Islamic junior high school.Methods: This study used a non-experimental research type with a cross-sectional design. The sample in this study amounted to 47 teenagers responden at Islamic Junior High school Al-Irsyad Tawangmangu.Total sampling was used as sampling technique. The instruments used were The Revised Olweus Bully/Victim Questionnaire and also a self-confidence questionnaire. Data analysis used kendall tau test.Results: In this study, it was found that the majority of bullying in adolescent in Islamic Junior High School Al-Irsyad Tawangmangu was in the low category as many as 30 respondents with a percentage 63.8%. Confidence in adolescent at Islamic High School Al-Irsyad Tawangmangu majority in the medium category as many as 26 respondents with a percentage 55.3%. Kendall tau obtained p value= 0,05 and r value= 0.366. Teenagers who experience bullying in the low category tend to experience self-confidence in the moderate category as many as 17 respondents (56.7%). Conclusion: there were relationship between bullying with self confidence among teens in Al-Irsyad Tawangmangu Islamic junior high school.Keywords: bullying; self confidence; teenagers